CORRELATION OF DIGITAL RECTAL EXAMINATION AND ANORECTAL MANOMETRY WITH PATIENTS REPORTED OUTCOMES AMONG WOMEN WITH FECAL INCONTINENCE - HASHMI, A; ARA, F; SAIFULLAH, S; IRAM, R; KAMAL, R; SHOAIB, M (Biological and Clinical Sciences Research Journal, 2024)
Fecal incontinence (FI), defined as the involuntary loss of bowel control leading to the accidental passage of stool, is a prevalent yet underreported condition, particularly among women. Objective: This study aims to investigate the correlation between findings from DRE and ARM with PROs in women suffering from FI. Methods: This cross-sectional, observational study was conducted at the Sandeman Provincial Hospital, Quetta from from 1 January 2024 to 30 June 2024. Data were collected from 60 patients. Results: Data were collected from 60 patients with a mean age of 52.5 ± 9.8 years and a mean body mass index (BMI) of 28.5 ± 4.1 kg/m². Additionally, 70% of the participants had been experiencing fecal incontinence for over two years. The Digital Rectal Examination (DRE) findings showed that 33.3% of participants (n = 20) had normal sphincter tone, while 41.7% (n = 25) exhibited moderate sphincter weakness. Severe sphincter weakness was observed in 25% (n = 15) of the participants. Conclusion: Both DRE and ARM are valuable diagnostic tools for assessing FI, with ARM showing a stronger correlation with PROs. Incorporating PROs into clinical evaluations enhances the understanding of FI’s impact and allows for more personalized treatment approaches. Further research with larger sample sizes is recommended to confirm these findings and improve management strategies.